Awareness of performance on outcomes after total hip and knee arthroplasty among Dutch orthopedic surgeons: how to improve feedback from arthroplasty registries - Van Schie, Peter; Van Bodegom-Vos, Leti; Zijdeman, Tristan M; Nelissen, Rob G H H (Acta Orthopaedica, 2020)
Background and purpose — The Netherlands Registry of Orthopedic Implants (LROI) uses audit and feedback (A&F) as the strategy to improve performance outcomes after total hip and knee arthroplasty (THA/TKA). Effectiveness of A&F depends on awareness of below-average performance to initiate improvement activities. We explored the awareness of Dutch orthopedic surgeons regarding their performance on outcomes after THA/TKA and factors associated with this awareness. Methods — An anonymous questionnaire was sent to all 445 eligible Dutch orthopedic surgeons performing THA/ TKA. To assess awareness on own surgeon-group performance, they were asked whether their 1-year THA/TKA revision rates over the past 2 years were below average (negative outlier), average (non-outlier), above average (positive outlier) in the funnel plot on the LROI dashboard, or did not know. Associations were determined with (1) dashboard login at least once a year (yes/no); (2) correct funnel-plot interpretation (yes/no) and; (3) recall of their 1-year THA/ TKA revision rate (yes/no). Results — 44% of respondents started the questionnaire, 158 THA and 156 TKA surgeons. 55% of THA surgeons and 55% of TKA surgeons were aware of their performance. Surgeons aware of their performance more often logged in on the LROI dashboard, more often interpreted funnel plots correctly, and more often recalled their revision rate. 38% of THA and 26% of TKA surgeons scored “good” on all 3 outcomes. Interpretation — Only half of the orthopedic surgeons were aware of their performance status regarding outcomes after THA/TKA. This suggests that to increase awareness, orthopedic surgeons need to be actively motivated to look at the dashboard more frequently and educated on interpretation of funnel plots for audit and feedback to be effective.